2013
DOI: 10.5455/medarh.2013.67.423-427
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Body Mass Index and Calcium Nephrolithiasis in Adult Population

Abstract: Introduction:Prevalence of the kidney stones (renal calculi) increase in several countries in parallel with the increase of overweight, diabetes (type 2 diabetes) and hypertension.Goal:The goal of our research was to evaluate the connection between the calcium nephrolithiasis and overweight, as quantified using the Body Mass Index (BMI) of the adult population, with a particular reflection on the age groups within it.Material and methods:The research was prospective and it was implemented at the Clinical Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Our research demonstrates that the average BMI of patients with bilateral kidney stones (26.23 ± 3.53kg/m 2 ) is signi cantly higher than that of patients with unilateral kidney stones (25.82 ± 3.52kg/m 2 ). This is consistent with reports written by Milicevic, S et al and Scales CD Jr et al 1,7 . That is, obesity, overweight, and kidney stones are related, and as BMI increases, urinary calcium and uric acid excretion increases, and the incidence and recurrence rate of urolithiasis are also rising.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our research demonstrates that the average BMI of patients with bilateral kidney stones (26.23 ± 3.53kg/m 2 ) is signi cantly higher than that of patients with unilateral kidney stones (25.82 ± 3.52kg/m 2 ). This is consistent with reports written by Milicevic, S et al and Scales CD Jr et al 1,7 . That is, obesity, overweight, and kidney stones are related, and as BMI increases, urinary calcium and uric acid excretion increases, and the incidence and recurrence rate of urolithiasis are also rising.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, an increasing number of studies have illustrated that chronic diseases such as metabolic syndrome (MetS), hypertension, diabetes mellitus (DM), obesity, gout, and chronic kidney disease are signi cantly related to kidney stones' occurrence and development [6][7][8][9][10] . Shimizu, T et al reported that hyperuricemia is the leading cause of gout.…”
Section: Introductionmentioning
confidence: 99%
“…For years overweight and obesity have been considered protective factors for bones and osteoporosis development. Nevertheless, new studies show that obesity, being one of main components of metabolic syndrome, has negative eff ects on bones despite normal values of bone mineral density (BMD) measured by DEXA method, which is considered to be the consequence of increased mechanical pressure on the bone (28,29). Ong et al think that higher BMD is not protective factor for osteoporotic fractures, for signifi cant number of such fractures occurs in obese women due to body habitus or mechanism of injury (30).…”
Section: Overweight and Obesitymentioning
confidence: 99%
“…“Radiopaque” includes calcium stones (calcium oxalate dihydrate, calcium oxalate monohydrate, calcium phosphate), “poor radiopacity” magnesium ammonium phosphate, apatite and cystine, while “radiolucent” includes urine acid, ammonium urate, xanthine, 2,8-dihydroxyadenine and drug-stones ( 5 ). The sensitivity and specificity of KUB radiography is 44-77% and 80-87% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%